Development of Digital Booklet Teaching Materials the Battle of Sunda Straits 1942 Based on Local History at SMAN 1 Ciomas - Magla, Lulu; Fadillah, Moh. Ali; Maryuni, Yuni (HISTORIA: Jurnal Program Studi Pendidikan Sejarah, 2026)
This research is motivated byThe problem with the school's objects is the lack of varied teaching materials and knowledge about local history material that is not widely known.To overcome these problems, the teaching materials offered by the researcher are teaching materials in the form of digital booklets containing a historical event in the Sunda Strait. The type of research used is R&D (Research and Development) research using the ADDIE model (analysis, design, development, implementation, evaluation). Based on the assessment of the feasibility of the material expert getting a score of 91%, the language expert getting a score of 98%, and the media expert getting a score of 88%, then the results were obtained that the three expert validators gave an assessment in the category of "very feasible". The results of the assessment of the teacher's practicality test are included in the category of "very practical" with a percentage of 83%. While the results of the practicality assessment of 28 students are included in the category of "very practical" with a percentage of 88.3% and are able to attract student motivation in using digital booklet teaching materials in history learning.